Variational iteration method for solving fisher equation - Selamat, Mat Salim (Universiti Teknologi MARA, 2009)
In this article, the variational iteration method (VIM) is applied to obtain an exact solution to Fisher equation. The result is compared to solution results by Adomian decomposition method (ADM).